All-solid battery and method for manufacturing the same
Patent Information
- Application Number
- CN202210413043.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-26
- Filing Date
- 2022-04-19
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-04-19
AI Technical Summary
因此,难以使使用了有机固体电解质的全固体电池在25℃的环境下工作
Smart Images

Figure CN115249808B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to all-solid-state batteries and methods for manufacturing the same, and particularly to all-solid-state batteries using a positive electrode layer, a negative electrode layer, and a solid electrolyte layer, and methods for manufacturing the same. Background Technology
[0002] In recent years, the lightweighting and wireless nature of electronic devices such as computers and mobile phones has created a need for reusable secondary batteries. These secondary batteries include nickel-cadmium batteries, nickel-metal hydride batteries, lead-acid batteries, and lithium-ion batteries. Among these, lithium-ion batteries have attracted significant attention due to their lightweight, high voltage, and high energy density.
[0003] In the automotive sector, such as electric vehicles and hybrid vehicles, the development of high-capacity rechargeable batteries is also gaining attention, and the demand for lithium-ion batteries is trending upward.
[0004] Lithium-ion batteries consist of a positive electrode layer, a negative electrode layer, and an electrolyte disposed between them. The electrolyte may be a liquid electrolyte containing a supporting electrolyte such as lithium hexafluorophosphate dissolved in an organic solvent, or a solid electrolyte. Currently, widely used lithium-ion batteries use electrolytes containing organic solvents, which are therefore flammable. Thus, materials, structures, and systems are needed to ensure the safety of lithium-ion batteries. In contrast, it is hoped that using non-flammable solid electrolytes will simplify the aforementioned materials, structures, and systems, and will lead to increased energy density, reduced manufacturing costs, and improved productivity. Hereinafter, batteries using solid electrolytes, such as lithium-ion batteries, will be referred to as "all-solid-state batteries."
[0005] Solid electrolytes can be broadly classified into organic solid electrolytes and inorganic solid electrolytes. Organic solid electrolytes have an ionic conductivity of 10⁻⁶ at 25°C. -6 The conductivity is approximately S / cm, and the ionic conductivity with the electrolyte is 10. -3 Compared to approximately S / cm, the ionic conductivity is extremely low. Therefore, it is difficult to operate all-solid-state batteries using organic solid electrolytes at 25°C. Inorganic solid electrolytes are generally oxide-based, sulfide-based, and halide-based solid electrolytes. Their ionic conductivity is 10... -4 ~10 -3 With a conductivity of around S / cm, they exhibit high ionic conductivity. Therefore, in recent years, there has been active research and development towards large-scale, high-capacity all-solid-state batteries utilizing these properties.
[0006] For example, Patent Document 1 discloses the structure of the solid electrolyte layer in an all-solid-state battery in which a positive electrode layer, a solid electrolyte layer, and a negative electrode layer are stacked in sequence. Patent Document 1 shows a structure that prevents peeling and crack propagation caused by the expansion and contraction of the positive and negative electrode layers during battery charging and discharging by forming through holes in the solid electrolyte layer, thereby preventing a decrease in battery capacity.
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent Application Publication No. 2014-86174 Summary of the Invention
[0010] One aspect of the present invention relates to an all-solid-state battery having a structure consisting of a positive current collector, a positive electrode layer comprising a positive active material and a first solid electrolyte, a solid electrolyte layer comprising a third solid electrolyte, a negative electrode layer comprising a negative active material and a second solid electrolyte, and a negative current collector, wherein the solid electrolyte layer has a repeating structure in which a low porosity portion and a high porosity portion having a higher porosity than the low porosity portion are repeatedly stacked in the in-plane direction. Attached Figure Description
[0011] Figure 1 This is a schematic diagram showing the cross-section of the all-solid-state battery in the embodiment.
[0012] Figure 2A This is a cross-sectional schematic diagram illustrating the process of forming the positive electrode layer in the implementation method.
[0013] Figure 2B This is a cross-sectional schematic diagram illustrating the process of forming the negative electrode layer in the implementation method.
[0014] Figure 2C This is a cross-sectional schematic diagram illustrating the solid electrolyte layer film formation process in the embodiment.
[0015] Figure 2D This is a cross-sectional schematic diagram used to illustrate the lamination and pressing processes in the implementation method.
[0016] Figure 3 This is a figure showing SEM images of the surface of the pre-pressurized powder film and the laser-sintered film in the embodiment.
[0017] Figure 4 This is a schematic diagram representing the necking state of particles in a solid electrolyte.
[0018] Figure 5 This is a schematic diagram showing the morphology of the solid electrolyte particles during the formation of the solid electrolyte layer in the embodiment.
[0019] Figure 6 This is a schematic diagram illustrating an example of the configuration of the low porosity portion and the high porosity portion of the solid electrolyte layer in the embodiment, viewed from top view.
[0020] Figure 7 This is a schematic diagram illustrating an example of the arrangement of low-porosity and high-porosity portions in a cross-section of the solid electrolyte layer in the embodiment.
[0021] Explanation of reference numerals in the attached figures
[0022] 1, 2, 5 Solid electrolytes
[0023] 3. Positive electrode active material
[0024] 4. Negative electrode active material
[0025] 6 Positive current collector
[0026] 7. Negative current collector
[0027] 10 Solid electrolyte layer
[0028] 11 Low porosity section
[0029] 12 High porosity section
[0030] 14 powder film
[0031] 15 Pre-pressurized powder membrane
[0032] 16 Laser-Sintered Films
[0033] 17 Space
[0034] 18 lasers
[0035] Parts 19 and 19a
[0036] 20 Positive electrode layer
[0037] 30 Negative Electrode Layer
[0038] 100 All-Solid-State Battery
[0039] Parts A and B
[0040] C Neck width Detailed Implementation
[0041] Generally, during the charge and discharge process of an all-solid-state battery, the positive active material in the positive electrode layer and / or the negative active material in the negative electrode layer expands and contracts due to repeated charge and discharge cycles. This makes it easy for delamination and cracking to occur at the interface between the positive electrode layer and the solid electrolyte layer, and / or the interface between the negative electrode layer and the solid electrolyte layer. With further repeated charge and discharge cycles, these delaminations and cracks propagate and expand, leading to a decrease in battery capacity.
[0042] As a countermeasure to prevent the propagation of such peeling and cracks, the structure shown in Patent Document 1 can be cited as an example. The all-solid-state battery disclosed in Patent Document 1 has a structure in which the solid electrolyte layer formed between the positive and negative electrode layers has through-holes, which make peeling and crack propagation less likely. However, the rapid expansion, contraction, and heating of the positive and / or negative electrode active materials caused by localized current concentration near these through-holes may increase the number of sites where peeling and cracks occur. In particular, the higher the charge / discharge capacity and charge / discharge rate, the more likely the above-mentioned problems will occur.
[0043] Therefore, the present invention provides an all-solid-state battery capable of suppressing the occurrence of peeling and cracking, and suppressing the propagation of existing peeling and cracking.
[0044] (Summary of the Invention)
[0045] The following is a summary of one aspect of the present invention.
[0046] One embodiment of the present invention provides an all-solid-state battery having a structure consisting of a positive current collector, a positive electrode layer comprising a positive active material and a first solid electrolyte, a solid electrolyte layer comprising a third solid electrolyte, a negative electrode layer comprising a negative active material and a second solid electrolyte, and a negative current collector, wherein the solid electrolyte layer has a repeating structure in which a low porosity portion and a high porosity portion having a higher porosity than the low porosity portion are repeatedly stacked in the in-plane direction.
[0047] Therefore, the low porosity portions that repeatedly exist in the in-plane direction within the solid electrolyte layer, while ensuring ion mobility during charging and discharging in the high porosity portions, suppress localized current concentration, thereby inhibiting layer delamination and cracking. Furthermore, at the interfaces between the positive and / or negative electrode layers in the solid electrolyte layer, stress caused by the expansion and contraction of the positive active material in the positive electrode layer and / or the negative active material in the negative electrode layer may occur. The high porosity portions within the solid electrolyte layer mitigate this stress, suppressing the propagation of delamination and cracks even in the event of delamination and cracking.
[0048] In addition, for example, the difference between the porosity of the high porosity portion and the porosity of the low porosity portion can be more than 5% and less than 40%.
[0049] Therefore, it is not easy to damage the battery performance of the all-solid-state battery, and it can effectively suppress the occurrence of the above-mentioned peeling and cracking, as well as the propagation of the peeling and cracking that have occurred.
[0050] Additionally, for example, the aforementioned low porosity portions can be arranged in a linear or dotted pattern when viewed from above.
[0051] This simplifies the apparatus used to form the low porosity portion.
[0052] Furthermore, for example, in the aforementioned repetitive structure, the ratio of the low porosity portion to the high porosity portion may differ between the outer periphery and the center of the solid electrolyte layer in a top view.
[0053] Therefore, by combining the characteristics and shape of all-solid-state batteries, it is possible to adjust the stress relief caused by the expansion and contraction of the active material and the balance between the ionic conductivity of the solid electrolyte layer.
[0054] Additionally, for example, at least one of the surfaces of the positive electrode layer and the negative electrode layer in the solid electrolyte layer may have an uneven shape.
[0055] As a result, the contact area between the solid electrolyte layer and the layer adjacent to the surface of the solid electrolyte layer increases, the battery performance is improved, and the occurrence of delamination can be further suppressed.
[0056] Additionally, for example, in the aforementioned concave-convex shape, the convex portion can be formed from the aforementioned low porosity portion.
[0057] As a result, the convex portion has a low porosity, making it easy to maintain its convex shape even under stress during the manufacturing process and use of the all-solid-state battery.
[0058] Additionally, for example, the solid electrolyte layer may have a portion with a higher porosity than the low porosity portion, which is parallel to the low porosity portion along the thickness direction and is in contact with the positive electrode layer or the negative electrode layer.
[0059] Therefore, the solid electrolyte layer can effectively mitigate the stress caused by the expansion and contraction of the active material at the interface between the positive electrode layer and the negative electrode layer in the solid electrolyte layer.
[0060] Additionally, for example, the solid electrolyte layer may have a portion with a lower porosity than the high porosity portion, which is parallel to the high porosity portion along the thickness direction and is in contact with the positive electrode layer or the negative electrode layer.
[0061] This can increase the ionic conductivity of the solid electrolyte layer near the positive and negative electrode layers, making it more difficult for local current concentration to occur.
[0062] In addition, one embodiment of the present invention provides a method for manufacturing an all-solid-state battery, which includes: a solid electrolyte powder film forming step in which a third solid electrolyte formed from a plurality of particles is spread into a film to form a powder film; a solid electrolyte pre-pressurizing step in which the powder film is pressurized to form a pre-pressurized powder film; and a solid electrolyte laser irradiation step in which the pre-pressurized powder film is irradiated with a laser to form a laser sintering film in which the particles of the third solid electrolyte are partially sintered together.
[0063] Therefore, laser irradiation promotes the sintering of the particles of the third solid electrolyte, reducing the space between the particles. This allows for the easy fabrication of a solid electrolyte layer with a repeating structure of low-porosity and high-porosity portions in the in-plane direction. Furthermore, it eliminates the need to partially replace materials to form the repeating structure, and the configuration of the low-porosity and high-porosity portions can be easily varied according to battery specifications such as the size of the all-solid-state battery and charge / discharge conditions to manufacture an all-solid-state battery.
[0064] Alternatively, for example, the manufacturing method described above may also include a solid electrolyte pressing step for pressing the laser-sintered film.
[0065] This improves the ionic conductivity of the solid electrolyte layer.
[0066] The following provides a detailed description of the all-solid-state battery in the embodiments. It should be noted that the embodiments described below are general or specific examples. The numerical values, shapes, materials, constituent elements, arrangement and connection methods of constituent elements, and processes shown in the following embodiments are examples and are not intended to limit the present invention.
[0067] Furthermore, in this specification, terms such as parallelism indicating the relationship between elements, and terms such as rectangle indicating the shape of elements, as well as numerical ranges, are not merely expressions in a strict sense, but rather expressions indicating substantially equal ranges, including, for example, expressions of differences of several percent.
[0068] Furthermore, the figures are schematic diagrams that have been appropriately emphasized, omitted, or proportionally adjusted for the purpose of illustrating the invention, and are not necessarily strict illustrations. Sometimes they differ from the actual shapes, positional relationships, and proportions. In each figure, substantially identical components are given the same symbols, and sometimes repeated descriptions are omitted or simplified.
[0069] Furthermore, in this specification, the terms "upper" and "lower" in the context of the all-solid-state battery configuration do not refer to the absolute spatial orientation of "upper" (vertically above) and "lower" (vertically below), but are used as terms defined by relative positional relationships based on the stacking order in a layered configuration. Additionally, the terms "upper" and "lower" apply not only to cases where two components are closely fitted together and in contact, but also to cases where two components are spaced apart and other components exist between them.
[0070] In addition, the cross-sectional view in this specification is a view showing the cross-section when the center of the all-solid-state battery is cut along the stacking direction, that is, the thickness direction of each layer.
[0071] (Implementation Method)
[0072] <Composition>
[0073] [A. All-solid-state battery]
[0074] For an overview of the all-solid-state battery in this embodiment, using Figure 1 Please provide an explanation. Figure 1 This is a schematic diagram showing a cross-section of the all-solid-state battery 100 in this embodiment. The all-solid-state battery 100 in this embodiment includes a positive current collector 6, a negative current collector 7, a positive electrode layer 20, a negative electrode layer 30, and a solid electrolyte layer 10. The positive electrode layer 20 is formed on the surface of the positive current collector 6 near the negative current collector 7, and includes a positive active material 3 and a solid electrolyte 1. The negative electrode layer 30 is formed on the surface of the negative current collector 7 near the positive current collector 6, and includes a negative active material 4 and a solid electrolyte 5. The solid electrolyte layer 10 is disposed between the positive electrode layer 20 and the negative electrode layer 30, and includes at least a solid electrolyte 2 with ion conductivity. In other words, the all-solid-state battery 100 has a structure formed by sequentially stacking the positive current collector 6, the positive electrode layer 20, the solid electrolyte layer 10, the negative electrode layer 30, and the negative current collector 7. The solid electrolyte layer 10 is, for example, in contact with the positive electrode layer 20 and the negative electrode layer 30. Furthermore, the solid electrolyte layer 10 has a repeating structure in which a low porosity portion 11 and a high porosity portion 12 with a higher porosity than the low porosity portion 11 are repeatedly arranged in the in-plane direction. In other words, the in-plane direction is a direction orthogonal to the thickness direction of the solid electrolyte layer 10. In the repeating structure, in at least one predetermined direction orthogonal to the thickness direction of the solid electrolyte layer 10, the low porosity portion 11 and the high porosity portion 12 are repeatedly arranged.
[0075] It should be noted that in this embodiment, solid electrolyte 1 is an example of the first solid electrolyte, solid electrolyte 5 is an example of the second solid electrolyte, and solid electrolyte 2 is an example of the third solid electrolyte.
[0076] The all-solid-state battery 100 is formed, for example, by the following method. First, a positive electrode layer 20 containing a positive electrode active material 3 is formed on a positive electrode current collector 6 made of metal foil; a negative electrode layer 30 containing a negative electrode active material 4 is formed on a negative electrode current collector 7 made of metal foil; and a solid electrolyte layer 10 containing an ion-conducting solid electrolyte 2 is disposed between the positive electrode layer 20 and the negative electrode layer 30. Then, from the outside of the positive electrode current collector 6 and the negative electrode current collector 7, for example, a pressure of 100 MPa or more and 1000 MPa or less is applied to press at least one of the layers to a fill rate of 55% or more and less than 100%, thereby obtaining the all-solid-state battery 100. By setting the fill rate to 55% or more, the voids in the solid electrolyte layer 10, the positive electrode layer 20, or the negative electrode layer 30 are reduced, thus allowing for a large amount of ion conduction and electron conduction of lithium (Li) ions, etc., resulting in good charge-discharge characteristics. It should be noted that the fill rate refers to the proportion of the total volume in each layer, excluding the voids between materials. The detailed manufacturing method for the all-solid-state battery 100 will be described later.
[0077] The pressed solid-state battery 100 is fitted with terminals and housed in a casing. The casing for the solid-state battery 100 can be, for example, made of metal such as aluminum laminate, stainless steel (SUS), iron, or aluminum, or made of resin.
[0078] The solid electrolyte layer 10, positive electrode layer 20, and negative electrode layer 30 of the all-solid-state battery 100 in this embodiment will be described below.
[0079] [B. Solid electrolyte layer]
[0080] First, the solid electrolyte layer 10 will be described. In this embodiment, the solid electrolyte layer 10 includes a solid electrolyte 2 and may also include a binder.
[0081] [B-1. Solid Electrolyte]
[0082] The solid electrolyte 2 in this embodiment will be described. Examples of solid electrolyte materials used in solid electrolyte 2 include sulfide-based solid electrolytes, halide-based solid electrolytes, and oxide-based solid electrolytes, which are generally known materials. Any one of these three types can be used as the solid electrolyte material. The type of sulfide-based solid electrolyte in this embodiment is not particularly limited. Examples of sulfide-based solid electrolytes include Li₂S-SiS₂, LiI-Li₂S-SiS₂, LiI-Li₂S-P₂S₅, LiI-Li₂S-P₂O₅, LiI-Li₃PO₄-P₂S₅, and Li₂S-P₂S₅. In particular, from the viewpoint of excellent lithium ion conductivity, sulfide-based solid electrolytes may contain Li, P, and S. Furthermore, due to high reactivity and binding strength with binders, sulfide-based solid electrolytes may contain P₂S₅. It should be noted that the above description of "Li2S-P2S5" refers to a sulfide-based solid electrolyte composed of raw materials containing Li2S and P2S5, and the same applies to other descriptions.
[0083] In this embodiment, the aforementioned sulfide-based solid electrolyte is, for example, a sulfide-based glass-ceramic containing Li₂S and P₂S₅. The molar ratio of Li₂S to P₂S₅ can be in the range of 70:30 to 80:20 or 75:25 to 80:20. By setting the Li₂S to P₂S₅ ratio within this range, it is possible to maintain the Li concentration that affects battery characteristics while achieving a crystal structure with high ionic conductivity. Furthermore, by setting the Li₂S to P₂S₅ ratio within this range, it is easy to ensure the amount of P₂S₅ used for reaction and bonding with the binder.
[0084] Furthermore, the type of oxide-based solid electrolyte in this embodiment is not particularly limited. Examples of oxide-based solid electrolytes include, for instance, Li. 0.57 La 0.29 TiO3, Li7La3Zr2O 12 、Li7La3Zr 2-x Nb x O 12 、Li7La3Zr 2- x Ta x O 12 Li5La3Ta2O 12 Li3PO4, Li 1.5 Al 0.5 Ge 1.5 P3O 12 wait.
[0085] In addition, the solid electrolyte 2 is formed, for example, from multiple particles.
[0086] [B-2. Adhesive]
[0087] The adhesive used in this embodiment will be described. The adhesive has neither ionic nor electronic conductivity and serves as a bonding material that bonds the materials within the solid electrolyte layer 10 to each other and to other layers. Known battery adhesives can be used. Alternatively, the adhesive in this embodiment may contain a thermoplastic elastomer with functional groups incorporated to improve adhesion strength. These functional groups can be carbonyl groups. Furthermore, from the viewpoint of improving adhesion strength, the carbonyl group can be maleic anhydride. The oxygen atoms of the maleic anhydride in the adhesive react with the solid electrolyte 2, causing the solid electrolytes 2 to bond together via the adhesive, creating a structure in which the adhesive is disposed between the solid electrolytes 2, resulting in improved adhesion strength.
[0088] As thermoplastic elastomers, styrene-butadiene-styrene (SBS) and styrene-ethylene-butadiene-styrene (SEBS) can be used. This is because they have high bonding strength and high durability in battery cycling characteristics. Among thermoplastic elastomers, hydrogenated (hereinafter, hydrogenated) thermoplastic elastomers can be used. By using hydrogenated thermoplastic elastomers, reactivity and adhesion are improved, and solubility in the solvent used to form the solid electrolyte layer 10 is improved.
[0089] The amount of binder added can be, for example, 0.01% by mass or more and 5% by mass or less, 0.1% by mass or more and 3% by mass or less, or 0.1% by mass or more and 1% by mass or less. By setting the amount of binder added to 0.01% by mass or more, bonding via the binder is easier to achieve, and sufficient bonding strength is easily obtained. In addition, by setting the amount of binder added to 5% by mass or less, the reduction in battery characteristics such as charge-discharge characteristics is less likely to occur. Furthermore, even if the physical properties of the binder, such as hardness, tensile strength, and elongation at break, change in regions such as low temperature, the charge-discharge characteristics are less likely to decrease.
[0090] [C. Positive electrode layer]
[0091] Next, the positive electrode layer 20 in this embodiment will be described. The positive electrode layer 20 in this embodiment includes a solid electrolyte 1 and a positive electrode active material 3. Conductive additives such as acetylene black and Ketjen black (registered trademark) and binders for ensuring electronic conductivity can be further added to the positive electrode layer 20 as needed. Since excessive addition can affect battery performance, it is desirable to use only a small amount without affecting battery performance. The weight ratio of solid electrolyte 1 to positive electrode active material 3 is, for example, in the range of 50:50 to 5:95, and can be in the range of 30:70 to 10:90. Furthermore, the volume ratio of the positive electrode active material 3 to the total volume of the positive electrode active material 3 and the solid electrolyte 1 is, for example, 60% or more and 80% or less. With this volume ratio, both the lithium-ion conduction path and the electron conduction path in the positive electrode layer 20 are easily ensured.
[0092] The positive current collector 6 is made of, for example, a metal foil. As the metal foil, for example, stainless steel (SUS), aluminum, nickel, titanium, copper, etc., can be used.
[0093] [C-1. Solid electrolyte]
[0094] Solid electrolyte 1 is at least one of the solid electrolyte materials arbitrarily selected from [B-1. Solid Electrolytes] mentioned above, without any particular limitation. Solid electrolyte 1 may use, for example, the same solid electrolyte material as solid electrolyte 2. Solid electrolyte 1 and solid electrolyte 2 may also use different solid electrolyte materials. Furthermore, solid electrolyte 1 is formed from a plurality of particles.
[0095] [C-2. Adhesive]
[0096] Same as the adhesives described above, therefore descriptions are omitted.
[0097] [C-3. Positive electrode active material]
[0098] The positive electrode active material 3 in this embodiment will be described. As the material of the positive electrode active material 3 in this embodiment, a lithium-containing transition metal oxide, for example, can be used. Examples of lithium-containing transition metal oxides include LiCoO2, LiNiO2, LiMn2O4, and LiC. o PO4, LiNiPO4, LiFePO4, LiMnPO4, and compounds obtained by replacing the transition metals of these compounds with one or two different types of elements. As compounds obtained by replacing the transition metals of the above compounds with one or two different types of elements, LiNi can be used. 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.8 Co0.15 Al 0.05 O2, LiNi 0.5 Mn 1.5 O2 and other known materials. One type of material can be used for the positive electrode active material 3, or two or more types can be used in combination.
[0099] Furthermore, the positive electrode active material 3 is formed, for example, from multiple particles. The particle size of the positive electrode active material 3 is not particularly limited, for example, it is 1 μm or more and 10 μm or less.
[0100] [D. Negative electrode layer]
[0101] Next, the negative electrode layer 30 in this embodiment will be described. The negative electrode layer 30 in this embodiment includes a solid electrolyte 5 and a negative electrode active material 4. Conductive additives such as acetylene black and Ketjen black, and binders, can be further added to the negative electrode layer 30 as needed to ensure electronic conductivity. Since excessive addition can affect battery performance, it is desirable to add only small amounts, to the point where it does not affect battery performance. The ratio of solid electrolyte 5 to negative electrode active material 4, by weight, is, for example, in the range of 5:95 to 60:40, and can be in the range of 30:70 to 50:50. Furthermore, the volume ratio of the negative electrode active material 4 to the total volume of the negative electrode active material 4 and the solid electrolyte 1 is, for example, 60% or more and 80% or less. With this volume ratio, both the lithium-ion conduction path and the electron conduction path within the negative electrode layer 30 are easily ensured.
[0102] The negative current collector 7 is made of, for example, a metal foil. As the metal foil, metal foils such as SUS, copper, and nickel can be used.
[0103] [D-1. Solid electrolyte]
[0104] Solid electrolyte 5 is at least one of the solid electrolyte materials arbitrarily selected from [B-1. Solid Electrolytes] above, without any particular limitation. Solid electrolyte 5 may use, for example, the same solid electrolyte material as solid electrolyte 1 and solid electrolyte 2. Solid electrolyte 5, solid electrolyte 1, and solid electrolyte 2 may also use different solid electrolyte materials from each other. Furthermore, solid electrolyte 5 may be formed, for example, from multiple particles.
[0105] [D-2. Adhesive]
[0106] The adhesive is the same as described above, so a description is omitted.
[0107] [D-3. Negative Electrode Active Material]
[0108] The negative electrode active material 4 in this embodiment will be described. As the material of the negative electrode active material 4 in this embodiment, materials such as indium, tin, silicon, and other metals that are easily alloyed with lithium, hard carbon, graphite, or lithium, or Li4Ti5O can be used. 12 SiO x Materials from public intellectuals, etc.
[0109] Furthermore, the negative electrode active material 4 is formed, for example, by multiple particles. The particle size of the negative electrode active material 4 is not particularly limited, for example, it is 1 μm or more and 15 μm or less.
[0110] <Manufacturing Method>
[0111] Next, the manufacturing method of the all-solid-state battery 100 in this embodiment will be described. Specifically, the manufacturing method of the all-solid-state battery 100 having a solid electrolyte layer 10, a positive electrode layer 20, and a negative electrode layer 30 will be described. Figure 2A This is a cross-sectional schematic diagram illustrating the process of forming the positive electrode layer 20 in the manufacturing method of the all-solid-state battery 100. Figure 2B This is a cross-sectional schematic diagram illustrating the process of forming the negative electrode layer 30 in the manufacturing method of the all-solid-state battery 100. Figure 2C This is a cross-sectional schematic diagram illustrating the solid electrolyte layer film formation process in the manufacturing method of the all-solid-state battery 100. Figure 2D This is a cross-sectional schematic diagram illustrating the lamination and pressing processes in the manufacturing method of the all-solid-state battery 100.
[0112] The manufacturing method of the all-solid-state battery 100 includes, for example, a positive electrode layer film formation process, a positive electrode layer pre-pressurization process, a negative electrode layer film formation process, a negative electrode layer pre-pressurization process, a solid electrolyte layer film formation process, a lamination process, and a pressing process.
[0113] Positive electrode layer film formation process ( Figure 2A In (a)), a positive electrode layer 20 is formed on the positive current collector 6. The positive electrode layer pre-pressurization process ( Figure 2A In (b)), the positive electrode layer 20 is pressurized and compressed within the range that can be handled in subsequent processes.
[0114] In addition, the negative electrode layer film formation process ( Figure 2B In step (c), a negative electrode layer 30 is formed on the negative electrode current collector 7. The negative electrode layer pre-pressurization process ( Figure 2B In (d), the negative electrode layer 30 is pressurized and compressed within the range that can be processed in subsequent processes.
[0115] Furthermore, in the solid electrolyte layer film formation process ( Figure 2CIn steps (e) to (h), a solid electrolyte layer 10 is formed. The solid electrolyte layer film formation process includes, for example, a solid electrolyte powder film formation process, a solid electrolyte pre-pressurization process, a solid electrolyte laser irradiation process, and a solid electrolyte pressing process. In the solid electrolyte powder film formation process ( Figure 2C In step (e), a solid electrolyte 2, composed of multiple particles, is spread into a film to form a powder film 14. In the solid electrolyte pre-pressurization process ( Figure 2C In step (f), the powder film 14 is pressurized at a specified pressure to form a pre-pressurized powder film 15. In the solid electrolyte laser irradiation process ( Figure 2C In the process (g), a laser-sintered film 16 is formed by irradiating multiple points of the pre-pressed powder film 15 with laser light, thereby partially sintering the particles of the solid electrolyte 2 together. In the solid electrolyte pressing process (g) Figure 2C In step (h), the laser-sintered film 16 is pressed under a specified pressure. Through this process, a solid electrolyte layer 10 is formed. During the solid electrolyte pressing process, heating can be applied as needed.
[0116] In the solid electrolyte layer film formation process, for example, the pressurization conditions in the solid electrolyte pre-pressurization process and the laser irradiation conditions in the solid electrolyte laser irradiation process are adjusted in such a way that the solid electrolyte layer 10 has a repeating structure in which a low porosity portion 11 and a high porosity portion 12 are repeatedly arranged in the in-plane direction.
[0117] Next, in the lamination and pressing processes ( Figure 2D In (i) and (j)), the positive electrode layer 20 formed on the positive electrode current collector 6, the negative electrode layer 30 formed on the negative electrode current collector 7, and the solid electrolyte layer 10 formed are stacked together in such a way that the solid electrolyte layer 10 is arranged between the positive electrode layer 20 and the negative electrode layer 30, and are pressed from the outside of the positive electrode current collector 6 and the negative electrode current collector 7.
[0118] There are no particular limitations on the method of applying pressure in the above-mentioned processes; for example, it can be flat pressing or roller pressing.
[0119] Next, each process will be explained in detail.
[0120] [E1. Positive electrode layer film formation process]
[0121] First, such as Figure 2A As shown in (a), the positive electrode layer film formation process is performed. The following methods can be listed as the film formation process (positive electrode layer film formation process) of the positive electrode layer 20 in this embodiment.
[0122] The positive electrode layer film formation process includes, for example, an additive preparation process and a powder lamination process. In the additive preparation process, unslurried powdered solid electrolyte 1 and positive electrode active material 3 are prepared, and a binder and conductive additive (not shown) are further prepared as needed. The prepared materials are mixed while applying appropriate shear and pressure to create a positive electrode additive in which the positive electrode active material 3 and solid electrolyte 1 are uniformly dispersed. In the powder lamination process, the prepared positive electrode additive is uniformly laminated onto the positive electrode current collector 6 to obtain a laminate. Compared to the conventional wet coating method of coating a slurry dispersed in a solvent, manufacturing by laminating the powdered positive electrode additive into a film has the advantage of eliminating the need for a drying process and reducing manufacturing costs. Furthermore, it avoids the residue of solvents in the positive electrode layer 20 after film formation that could reduce the battery performance of the all-solid-state battery 100. It should be noted that slurried positive electrode additives can be laminated into a film to form the positive electrode layer 20.
[0123] [E2. Positive electrode layer pre-pressurization process]
[0124] Next, as Figure 2A As shown in (b), a positive electrode layer pre-pressurization process is performed. In the positive electrode layer pre-pressurization process, the laminate containing the positive electrode current collector 6, the solid electrolyte 1 and the positive electrode active material 3 obtained in the positive electrode layer film formation process is pressurized, thereby densifying the positive electrode powder to a level that is easy to process in subsequent processes, and forming the positive electrode layer 20 in the form of a powder compression film.
[0125] [F1. Negative electrode layer film formation process]
[0126] Next, as Figure 2B As shown in (c), the negative electrode layer film formation process is performed. The film formation process of the negative electrode layer 30 in this embodiment (negative electrode layer film formation process) is the same as that described above in [E1. positive electrode layer film formation process], except that the material used is changed to the material used for the negative electrode layer 30.
[0127] In other words, in the negative electrode layer film formation process, for example, a negative electrode mixture containing an unslurried powdered solid electrolyte 5, a negative electrode active material 4, and a binder and conductive additive (not shown) as needed is laminated onto the negative electrode current collector 7. It should be noted that the slurried negative electrode mixture can be formed into a film to form the negative electrode layer 30.
[0128] [F2. Negative electrode layer pre-pressurization process]
[0129] Next, as Figure 2BAs shown in (d), a negative electrode layer pre-pressurization process is performed. In the negative electrode layer pre-pressurization process, for example, the laminate containing the negative electrode current collector 7, the solid electrolyte 5, and the negative electrode active material 4 obtained in the negative electrode layer film formation process is pressurized to densify the powder to a level that is easy to handle in subsequent processes, thereby forming the negative electrode layer 30 in the form of a powder compression film. That is to say, the negative electrode layer pre-pressurization process can be the same method as that in [E2. Positive electrode layer pre-pressurization process].
[0130] [G. Solid electrolyte layer film formation process]
[0131] In the film-forming process of the solid electrolyte layer 10 (solid electrolyte layer film-forming process), a solid electrolyte 2 selected from the materials listed in [B-1. Solid electrolyte] is used. Furthermore, a mixture of solid electrolyte 2 and a binder as required is laminated onto at least one of the positive electrode layer 20 obtained in the positive electrode layer pre-pressurization process and the negative electrode layer 30 obtained in the negative electrode layer pre-pressurization process to form a film.
[0132] Figure 2C In the example shown, the solid electrolyte 2 is laminated as a film on the negative electrode layer 30, but this is not a limitation. In the solid electrolyte layer film-forming process, the solid electrolyte 2 may also be formed directly as a film on at least one of the positive electrode layer 20 and the negative electrode layer 30. Alternatively, in the solid electrolyte layer film-forming process, the solid electrolyte layer 10 may be formed on a support substrate different from the positive electrode layer 20 and the negative electrode layer 30, and then transferred from the support substrate to at least one of the positive electrode layer 20 and the negative electrode layer 30. The support substrate may be, for example, a polyethylene terephthalate (PET) film.
[0133] Here, the solid electrolyte layer film formation process is described in detail.
[0134] [G1. Solid Electrolyte Powder Film Formation Process]
[0135] First, such as Figure 2C As shown in (e), in the solid electrolyte powder film formation process, the solid electrolyte 2 formed by multiple particles is spread into a film to form a powder film 14. Figure 2C In the example shown in (e), the powder film 14 is formed on the negative electrode layer 30. Here, the method for laying the solid electrolyte 2 into a film is not particularly limited. Examples of methods for laying the solid electrolyte 2 into a film include, for instance, supplying powder of the solid electrolyte 2 and planarizing it using a rubber scraper or similar method.
[0136] [G2. Solid electrolyte pre-pressurization process]
[0137] Next, as Figure 2CAs shown in (f), in the solid electrolyte pre-pressurization process, the powder film 14 formed in the solid electrolyte powder film formation process is pressurized at a specified pressure to form a pre-pressurized powder film 15. The method of pressurization in the solid electrolyte pre-pressurization process is not particularly limited. Examples of pressurization methods in the solid electrolyte pre-pressurization process include flat pressing and roll pressing. The purpose of the solid electrolyte pre-pressurization process is to expel air from the powder film 14, making the particles of the solid electrolyte 2 constituting the powder film 14 more closely connected. Therefore, in the next process, the sinterability of the solid electrolyte 2 varies depending on the close contact state of the solid electrolyte 2 particles. The pressurization conditions in the solid electrolyte pre-pressurization process and the laser irradiation conditions in the solid electrolyte laser irradiation process are adjusted, for example, according to the material and particle size of the solid electrolyte 2.
[0138] [G3. Solid Electrolyte Laser Irradiation Process]
[0139] Next, as Figure 2C As shown in (g), in the solid electrolyte laser irradiation process, a laser is irradiated onto the pre-pressurized powder film 15 formed in the solid electrolyte pre-pressurization process, thereby forming a laser-sintered film 16 in which the particles of the solid electrolyte 2 constituting the pre-pressurized powder film 15 are partially sintered together. Here, by providing multiple laser-irradiated portions in the laser-sintered film 16, a structure is formed in which the portion where particle sintering is promoted and the portion where particle sintering is insufficient are alternately formed in the in-plane direction. In addition, by providing portions with high laser energy and portions with low laser energy, a structure is formed in which the portion where particle sintering is promoted and the portion where particle sintering is insufficient are alternately formed in the in-plane direction.
[0140] In the solid electrolyte laser irradiation process, for example, in areas where the irradiated laser energy is high, particle sintering is promoted, while in areas not irradiated by laser or where the irradiated laser energy is low, particle sintering is insufficient. As will be described in detail later, the porosity decreases in the regions where particle sintering is promoted, and the porosity increases in the regions where particle sintering is insufficient. This porosity relationship is a relative relationship compared to the regions where particle sintering is promoted and the regions where particle sintering is insufficient. This porosity relationship is maintained in the final manufactured all-solid-state battery 100; therefore, the regions where particle sintering is promoted are referred to as the low porosity regions 11, and the regions where particle sintering is insufficient are referred to as the high porosity regions 12.
[0141] [G4. Solid Electrolyte Pressing Process]
[0142] Next, as Figure 2CAs shown in (h), in the solid electrolyte pressing process, the solid electrolyte layer 10 is formed by pressing the laser-sintered film 16 formed in the solid electrolyte laser irradiation process under a specified pressure. The pressing pressure in the solid electrolyte pressing process is, for example, a pressure greater than the pressure applied in the solid electrolyte pre-pressurization process. Additionally, heating can be used to press the laser-sintered film 16 as needed.
[0143] In addition, the solid electrolyte pressing process can be combined with the pressing process described below, and can be omitted.
[0144] [H. Lamination and pressing processes]
[0145] Next, as Figure 2D As shown in (i) and (j), a lamination process and a pressing process are performed. In the lamination process, the positive electrode layer 20, the solid electrolyte layer 10, and the negative electrode layer 30 are stacked sequentially. In the pressing process, the laminated body is pressed. Specifically, in the lamination and pressing processes, the positive electrode layer 20 formed on the positive electrode current collector 6, the negative electrode layer 30 formed on the negative electrode current collector 7, and the solid electrolyte layer 10, obtained through each film formation process and each pre-pressing process, are stacked in such a way that the solid electrolyte layer 10 is arranged between the positive electrode layer 20 and the negative electrode layer 30 (lamination process), and then pressed from the outside of the positive electrode current collector 6 and the negative electrode current collector 7 (pressing process) to obtain an all-solid-state battery 100. It should be noted that when the solid electrolyte pressing process is omitted, the pressing process is combined with the solid electrolyte pressing process for pressing the laser sintered film 16.
[0146] The purpose of pressing is to increase the density of the positive electrode layer 20, the negative electrode layer 30, and the solid electrolyte layer 10. By increasing the density, the lithium-ion conductivity and electronic conductivity in the positive electrode layer 20, the negative electrode layer 30, and the solid electrolyte layer 10 can be improved, resulting in an all-solid-state battery 100 with good battery characteristics.
[0147] <Research Results>
[0148] During the research on realizing the structure of the all-solid-state battery 100 according to this embodiment, the following laser-sintered film 16 was formed. As the solid electrolyte 2 constituting the laser-sintered film 16, Li₂, as an oxide-based solid electrolyte, was used. 0.57 La 0.29 TiO3 (lithium lanthanum titanium oxide: manufactured by Toho Titanium) particles.
[0149] First, oxide-based solid electrolyte particles (average particle size 0.9 μm) are deposited on a substrate, and the film thickness is adjusted using a rubber scraper to form a powder film 14 formed from the particles of solid electrolyte 2. Further, pre-pressurization is applied from the upper surface of the powder film 14 at a pressure of 1 kPa or more and 1000 kPa or less, for example, 100 kPa, to form a pre-pressurized powder film 15.
[0150] Next, a CO2 laser was used to scan the upper surface of the pre-pressurized powder film 15 in a stripe pattern and irradiate it to form a laser-sintered film 16. In addition, SEM (Scanning Electron Microscope) observations were performed on the surface of the pre-pressurized powder film 15 before and after laser irradiation. Figure 3 This is a figure showing SEM images of the surfaces of the pre-pressurized powder film 15 and the laser-sintered film 16. Figure 3 (a) is a SEM image of the upper surface of the pre-pressurized powder film 15 before laser irradiation. Figure 3 (b) is a SEM image of the upper surface of the laser sintered film 16 formed by irradiating the pre-pressurized powder film 15 with a laser.
[0151] The results of surface SEM observation are as follows: Figure 3 As shown in (a), the pre-pressurized powder film 15 before laser irradiation is in a state where the particles of the oxide-based solid electrolyte are uniformly distributed. On the other hand, as Figure 3 As shown in (b), it was confirmed that in the laser-sintered film 16, the particles of the solid electrolyte 2 undergo necking-to-each-each-other by laser irradiation, and the sintered portion A and the portion B where the necking-to-each-other of the solid electrolyte 2 particles is not fully achieved are alternately formed in the in-plane direction. Furthermore, it was confirmed that the surface of the laser-sintered film 16 has an uneven structure resulting from portions A and B. On the surface of the laser-sintered film 16, portion A is a convex portion, and portion B is a concave portion.
[0152] Here, on Figure 3 (b) shows the necking state of the particles of solid electrolyte 2 in portions A and B. Figure 4 Please provide an explanation. Figure 4 This is a schematic diagram representing the necking state of the particles in solid electrolyte 2. For example... Figure 4 As shown, the necking of particles in solid electrolyte 2 refers to the phenomenon where particles bind together, forming a necked shape between the bound particles. Furthermore, the necking process occurs because the binding of particles continues, thus increasing the width of the necked portion, i.e., the necking width. Therefore, for... Figure 4 The necking width C shown is, if for Figure 3 Comparing part A with part B as shown in (b), it is confirmed that the necking width C of solid electrolyte 2 in part A is more than 1.5 times that of solid electrolyte 2 in part B.
[0153] Next, regarding the behavior mechanism of the particles in solid electrolyte 2 under laser irradiation, the following was discussed: Figure 5 Please provide an explanation. Figure 5 This is a schematic diagram showing the state of the particles of solid electrolyte 2 during the formation of solid electrolyte layer 10. Figure 5 The illustration of the substrate is omitted in the text.
[0154] Figure 5 (a) is a schematic diagram showing the state in which the particles of solid electrolyte 2 form a pre-pressurized powder film 15. Figure 5 As shown in (a), spaces 17 exist between the particles of the solid electrolyte 2 in the pre-pressurized powder film 15. By partially irradiating such a pre-pressurized powder film 15 with laser 18, a... Figure 5 The laser-sintered film 16 is shown in (b). Here, in the region 19 where the sintering of the solid electrolyte 2 is promoted by the irradiation of the laser 18, in other words, in the region 19 where the laser irradiation energy is strong, the particles of the solid electrolyte 2 undergo necking, and the necked particles of the solid electrolyte 2 are attracted to each other, while the space 17 decreases. In other words, in regions other than the region 19 where the laser irradiation energy is strong, that is, in regions where the laser irradiation energy is weaker than that of the laser irradiation energy irradiating region 19, or where no laser irradiation has occurred, the amount of solid electrolyte 2 particles is reduced, and the necking is not sufficient, so the reduction in space 17 is small. Therefore, in region 19, the porosity is lower, and in regions other than region 19, the porosity is higher than that of region 19. That is to say, in the laser-sintered film 16, it is possible to intentionally separate regions with high and low porosity. In addition, due to this difference in the amount of solid electrolyte 2 particles, the region 19 formed on the surface of the laser-sintered film 16 has a raised, uneven shape. It should be noted that different porosities can also be formed by pressing with a pressing plate or similar material with concave and convex shapes. In this case, unlike methods based on laser irradiation, the areas with higher porosity become concave sections.
[0155] Furthermore, such as Figure 5 As shown in (c), the laser-sintered film 16 is pressed at a pressure of 1 MPa or higher and 1000 MPa or lower to form a solid electrolyte layer 10. The absolute values of the porosity and the absolute values of the height of the unevenness of the solid electrolyte layer 10 change from the laser-sintered film 16, but the porosity and unevenness remain. In particular, since part 19 is a convex portion, part 19 is easily pressed, and the porosity of part 19 easily decreases through pressing. Through this process and the behavior of the solid electrolyte 2 particles, the aforementioned low-porosity portion 11 and high-porosity portion 12 are formed in the solid electrolyte layer 10. That is, Figure 5 Part 19a in (c) corresponds to the low porosity portion 11. Additionally, as... Figure 5 As shown in (c), due to the low porosity portion 11 and the high porosity portion 12, at least one of the surfaces on the positive electrode layer 20 side and the negative electrode layer 30 side of the solid electrolyte layer 10 has an uneven shape. Furthermore, in this uneven shape, the convex portion is formed by the low porosity portion 11, and the concave portion is formed by the high porosity portion 12. Therefore, because the convex portion has low porosity, the uneven shape is easily maintained even under stress during the manufacturing process and use of the all-solid-state battery 100.
[0156] Here, the difference in porosity between the low porosity portion 11 and the high porosity portion 12, as well as the size of the uneven shape, are adjusted by adjusting the pressure applied during the pre-pressurization process to form the pre-pressurized powder film 15, and the energy and irradiation interval of the laser irradiation to form the laser sintered film 16.
[0157] In this way, the solid electrolyte layer 10 formed using the above mechanism has a structure that partially has a low porosity portion 11 and a high porosity portion 12. The high porosity portion 12 mitigates the stress generated by the expansion and contraction of the active material during charging and discharging in the all-solid-state battery 100, and it is expected to suppress the occurrence and propagation of delamination and cracks. Furthermore, the uneven shape of the surface of the solid electrolyte layer 10 can also be expected to increase the contact area between the solid electrolyte layer and the positive electrode layer and / or negative electrode layer, thereby improving battery performance and reducing delamination.
[0158] Furthermore, the porosity of the low porosity portion 11 is, for example, 5% or more and 20% or less. The porosity of the high porosity portion 12 is, for example, 25% or more and 45% or less. The difference between the porosity of the high porosity portion 12 and the porosity of the low porosity portion 11, expressed by the formula "porosity of high porosity portion 12" - "porosity of low porosity portion 11", is, for example, 5% or more and 40% or less. With this porosity difference being less than 40%, the ionic conductivity of the solid electrolyte layer 10 is less likely to decrease, and the battery performance of the all-solid-state battery 100 is less likely to be impaired. Furthermore, with this porosity difference being 5% or more, the effect of suppressing delamination and the occurrence and propagation of cracks can be improved. The porosity is measured, for example, by observing a cross-section of the solid electrolyte layer 10. For example, the porosity is defined as the percentage of the area of a given area of solid electrolyte 2 that does not occupy porosity.
[0159] Furthermore, the necking width of the particles in the low-porosity portion 11 of the solid electrolyte 2 is, for example, 1.5 times or more and 10 times or less than the necking width of the particles in the high-porosity portion 12 of the solid electrolyte 2. With this ratio of 1.5 times or more, the effect of suppressing the occurrence and propagation of peeling and cracks can be improved. Conversely, with this ratio of 10 times or less, the ionic conductivity of the high-porosity portion 12 is less likely to decrease, thus less likely to impair the battery performance of the all-solid-state battery 100.
[0160] Next, the configuration of the low porosity portion 11 and the high porosity portion 12 in the solid electrolyte layer 10 will be described. In the repeating structure of the solid electrolyte layer 10, the position and shape of the low porosity portion 11 and the high porosity portion 12 can be freely adjusted, for example, by adjusting the position of the irradiating laser.
[0161] For example, the low porosity portion 11 is arranged in a linear or dotted pattern. By arranging the low porosity portion 11 in such a shape, the apparatus for irradiating the laser used in forming the low porosity portion 11 can be simplified.
[0162] Furthermore, in the repeated structure, the ratio of the low porosity portion 11 to the high porosity portion 12 differs between the outer periphery and the center of the solid electrolyte layer 10 in top view. This allows for the adjustment of the stress relief caused by the expansion and contraction of the active material and the balance of the ionic conductivity of the solid electrolyte layer 10, based on the characteristics and shape of the all-solid-state battery 100. The ratio is, for example, an area ratio; and the center is, for example, a region further inward than a position equidistant from the center and outer periphery of the solid electrolyte layer 10 in top view, while the outer periphery is a region further outward than the center.
[0163] Here, for an example of the configuration of the low porosity portion 11 and the high porosity portion 12 in a top view of the solid electrolyte layer 10, using Figure 6 Please provide an explanation.
[0164] Figure 6 This is a schematic diagram showing an example of the configuration of the low porosity portion 11 and the high porosity portion 12 in a top view of the solid electrolyte layer 10. Figure 6 This is a diagram of the solid electrolyte layer 10 of the all-solid-state battery 100 as viewed from the top surface, that is, along the stacking direction.
[0165] For example, such as Figure 6 As shown in (a), the low porosity portion 11 and the high porosity portion 12 are arranged in a stripe pattern by scanning and irradiating with a laser in a stripe pattern during the laser irradiation process of the solid electrolyte layer. Figure 6The repeating structure shown in (a) is a linear structure in which low porosity portions 11 and high porosity portions 12 repeat along the in-plane direction of the solid electrolyte layer 10. With this configuration, the apparatus for irradiating the laser used in the formation of the low porosity portions 11 can be simplified, and the low porosity portions 11 and high porosity portions 12 can be formed more easily.
[0166] In addition, for example, Figure 6 As shown in (b), by scanning and irradiating the solid electrolyte layer with a laser in a ring shape during the laser irradiation process, in a top view, except for the high porosity portion 12 located at the center, the low porosity portion 11 and the high porosity portion 12 are arranged in a ring shape. Figure 6 In the example shown in (b), the annular shape is a rectangular ring shape, but it is not particularly limited and can be a similar shape to the outer periphery of the solid electrolyte layer 10 or a circular ring shape. With this configuration, during the solid electrolyte pressing process after laser irradiation, the material constituting the solid electrolyte layer 10 is less likely to flow from the center to the periphery in top view, and is less likely to damage the pressing pressure and film thickness uniformity at the center and the periphery.
[0167] In addition, for example, Figure 6 As shown in (c), by scanning and irradiating the solid electrolyte layer with laser in a radial pattern from the center outwards during the laser irradiation process, the low porosity portions 11 are arranged radially in plan view, with the high porosity portions 12 embedded between the radially arranged low porosity portions 11. With this arrangement, in plan view, as the area per unit area not irradiated by laser increases from the center outwards, in other words, the ratio of high porosity portions 12 to low porosity portions 11 increases. The stress caused by the expansion and necking of the active material in the all-solid-state battery 100 is greater closer to the outer periphery; therefore, as the proportion of high porosity portions 12 increases towards the outer periphery, the stress caused by expansion and necking is easily mitigated. In other words, this is effective for the large-scale development of the all-solid-state battery 100.
[0168] In addition, like the formation Figure 6 As shown in (a) to (c), the laser is not limited to being scanned and irradiated in a continuous linear pattern. By scanning and irradiating the laser in a dashed or dotted pattern, it is also expected to mitigate the strain caused by the local stress difference between the low porosity portion 11 and the high porosity portion 12.
[0169] Next, the arrangement of the low porosity portion 11 and the high porosity portion 12, etc., in the thickness direction of the solid electrolyte layer 10 will be described. By repeatedly performing the process described in [G. Solid Electrolyte Layer Formation Process] above, and forming the solid electrolyte layer 10 on the positive electrode layer 20 and the negative electrode layer 30 respectively by the method described in [G. Solid Electrolyte Layer Formation Process], a multi-layer solid electrolyte layer 10 can be formed. Therefore, the porosity can be varied along the thickness direction of the solid electrolyte layer 10. For example, the solid electrolyte layer 10 may include layers with a repeating structure and layers without a repeating structure. In the solid electrolyte layer 10, the layers without a repeating structure are arranged, for example, in contact with at least one of the positive electrode layer 20 and the negative electrode layer 30. For an example of the arrangement of the low porosity portion 11 and the high porosity portion 12 in the cross-section of the solid electrolyte layer 10, using Figure 7 Please provide an explanation.
[0170] Figure 7 This is a schematic diagram showing an example of the arrangement of the low porosity portion 11 and the high porosity portion 12 in a cross-section of the solid electrolyte layer 10. Figure 7 This is a diagram of a cross-section of the solid electrolyte layer 10 located between the positive electrode layer 20 and the negative electrode layer 30, cut along the thickness direction.
[0171] For example, such as Figure 7 As shown in (a), the positions in the solid electrolyte layer 10 that form the interface between the solid electrolyte layer 10 and the positive electrode layer 20 and the interface between the solid electrolyte layer 10 and the negative electrode layer 30 can be configured with layers composed of low porosity portions 11. Figure 7 The solid electrolyte layer 10 shown in (a) has a low porosity portion 11 that runs parallel to the high porosity portion 12 along the thickness direction and is in contact with the positive electrode layer 20 and the negative electrode layer 30. It should be noted that the low porosity portion 11 running parallel to the high porosity portion 12 along the thickness direction is simply a portion with a lower porosity than the high porosity portion 12, and its porosity may differ from that of the low porosity portion 11 in the repeating structure, i.e., the low porosity portion 11 running parallel to the high porosity portion 12 along the in-plane direction. Alternatively, the solid electrolyte layer 10 may be configured to not include either a layer composed of the low porosity portion 11 in contact with the positive electrode layer 20, or a layer composed of the low porosity portion 11 in contact with the negative electrode layer 30.
[0172] With this configuration, the ionic conductivity of the solid electrolyte layer 10 near the positive electrode layer 20 and the negative electrode layer 30 can be improved. When using a solid electrolyte 2 with low ionic conductivity, local current concentration at the interface between the solid electrolyte layer 10 and the positive electrode layer 20 and the interface between the solid electrolyte layer 10 and the negative electrode layer 30 is less likely to occur.
[0173] In addition, for example, Figure 7 As shown in (b), the positions in the solid electrolyte layer 10 that form the interface between the solid electrolyte layer 10 and the positive electrode layer 20 and the interface between the solid electrolyte layer 10 and the negative electrode layer 30 can also be configured with layers composed of high porosity portions 12. Figure 7 The solid electrolyte layer 10 shown in (b) has a high porosity portion 12 that runs parallel to the low porosity portion 11 along the thickness direction and is in contact with the positive electrode layer 20 and the negative electrode layer 30. It should be noted that the high porosity portion 12 running parallel to the low porosity portion 11 along the thickness direction is simply a portion with a higher porosity than the low porosity portion 11, and can be different from the porosity of the high porosity portion 12 in the repeating structure, i.e., the high porosity portion 12 running parallel to the low porosity portion 11 along the in-plane direction. Alternatively, the solid electrolyte layer 10 may be configured to not include either a layer composed of the high porosity portion 12 in contact with the positive electrode layer 20, or a layer composed of the high porosity portion 12 in contact with the negative electrode layer 30.
[0174] With this configuration, the stress caused by the expansion and contraction of the active material is easily mitigated near the interfaces of the solid electrolyte layer 10 and the positive electrode layer 20, and near the interfaces of the solid electrolyte layer 10 and the negative electrode layer 30. Furthermore, with this configuration, by using a material with high ionic conductivity as the solid electrolyte 2 constituting the solid electrolyte layer 10, the degradation of battery performance can be suppressed.
[0175] In addition, for example, Figure 7 As shown in (c), the solid electrolyte layer 10 is composed of multiple layers, each having a repeating structure, and can be arranged such that the low-porosity portions 11 and high-porosity portions 12 in adjacent layers are offset. By arranging them in this way, deviations in ionic conductivity caused by differences in the density of the solid electrolyte 2 in the in-plane direction of the solid electrolyte layer 10 can be suppressed, ensuring uniformity in the in-plane direction. Furthermore, Figure 7 The configurations shown in (a) to (c) can be combined appropriately.
[0176] Furthermore, by utilizing the idea of these configurations, by setting the ionic conductivity in the region at the end of the all-solid-state battery 100 (e.g., within 5 mm from the end face when viewed along the stacking direction) to be lower than that in other regions, it is possible to suppress unpredictable battery reactions via the ends of the positive electrode layer 20 and the negative electrode layer 30, and short-circuit suppression effects can also be expected.
[0177] (Other implementation methods)
[0178] The above description of the all-solid-state battery according to the present invention is based on embodiments, but the present invention is not limited to these embodiments. Various modifications to the embodiments that can be conceived by those skilled in the art, and other methods of constructing the embodiments by combining some of the constituent elements, are also included within the scope of the present invention, as long as they do not depart from the spirit of the invention.
[0179] For example, the above embodiment describes an example where lithium ions are conducted in the all-solid-state battery 100, but it is not limited thereto. The ions conducted in the all-solid-state battery 100 can be ions other than lithium ions, such as sodium ions, magnesium ions, potassium ions, calcium ions, or copper ions.
[0180] Furthermore, in the above embodiment, the repeating structure is formed by irradiating with a laser, but it is not limited to this. The repeating structure can be formed by using various solid electrolyte 2 materials or by adjusting the pressure conditions of the powder film 14.
[0181] According to the all-solid-state battery and the like of the present invention, it is possible to suppress the occurrence of peeling and cracking, as well as the propagation of the peeling and cracking that have occurred.
[0182] Industrial availability
[0183] The all-solid-state battery of this invention is expected to be used in various batteries such as power supplies for portable electronic devices and automotive batteries.
Claims
1. An all-solid-state battery having sequentially stacked layers Positive current collector, The positive electrode layer, containing positive electrode active material and the first solid electrolyte, A solid electrolyte layer containing a third solid electrolyte. The negative electrode layer contains the negative electrode active material and the second solid electrolyte, and The structure formed by the negative electrode current collector The solid electrolyte layer has an iterative structure in which low porosity portions and high porosity portions with higher porosity than the low porosity portions are repeatedly intersected in the in-plane direction. The low porosity portion has a porosity of 5% or more and 20% or less, while the high porosity portion has a porosity of 25% or more and 45% or less. At least one of the surfaces of the positive electrode layer and the negative electrode layer in the solid electrolyte layer has an uneven shape. In the concave-convex shape, the convex portion is formed by the low porosity portion, and the concave portion is formed by the high porosity portion.
2. The all-solid-state battery according to claim 1, wherein, The difference between the porosity of the high porosity portion and the porosity of the low porosity portion is more than 5% and less than 40%.
3. The all-solid-state battery according to claim 1 or 2, wherein, The low porosity portions are arranged in a linear or dotted pattern when viewed from above.
4. The all-solid-state battery according to claim 1 or 2, wherein, In the repetitive structure, the ratio of the low porosity portion to the high porosity portion differs between the outer periphery and the center of the solid electrolyte layer in a top view.
5. The all-solid-state battery according to claim 1 or 2, wherein, The solid electrolyte layer has a portion with a higher porosity than the low porosity portion, which is parallel to the low porosity portion along the thickness direction and is in contact with the positive electrode layer or the negative electrode layer.
6. The all-solid-state battery according to claim 1 or 2, wherein, The solid electrolyte layer has a portion with a lower porosity than the high porosity portion, which is parallel to the high porosity portion along the thickness direction and is in contact with the positive electrode layer or the negative electrode layer.
7. A method for manufacturing an all-solid-state battery, as described in claim 1. The process includes the following steps: In the solid electrolyte powder film formation process, a third solid electrolyte, which is formed from multiple particles, is spread into a film to form a powder film. The solid electrolyte pre-pressurization process involves pressurizing the powder membrane to form a pre-pressurized powder membrane; and The solid electrolyte laser irradiation process involves irradiating the pre-pressurized powder film with a laser to form a laser-sintered film in which the particles of the third solid electrolyte are partially sintered together.
8. The method for manufacturing an all-solid-state battery according to claim 7, wherein, Also includes: A solid electrolyte pressing process for pressing the laser-sintered film.
Citation Information
Patent Citations
All solid state battery and manufacturing method therefor
JP2014086174A
Solid electrolyte laminate sheet, all-solid-state secondary battery, and method for manufacturing all-solid-state secondary battery
CN116868407A
Solid electrolyte membrane and preparation method and application thereof
CN120674576A
Nonaqueous electrolyte battery
JP2013016280A
All-solid-state cell
WO2013175993A1